Group Counselling with Expressive Writing Therapy to Enhance Self-Acceptance of Junior High School Students from Broken Homes - Lisna Marselina Nasution; Nefi Darmayanti (Journal of General Education and Humanities, 2025)
This study aims to examine the effectiveness of group counselling with expressive writing therapy in enhancing self-acceptance among junior high school students from broken home families at Madrasah Aliah Al-Jam’iyatul Washliyah Tembung. A pre-experimental design, consisting of a one-group pretest–posttest, was employed, involving eight students selected through purposive sampling based on their low self-acceptance scores. The intervention consisted of four sessions of group counselling, each incorporating expressive writing exercises to explore emotions, reflect on personal experiences, and develop coping strategies. Pretest and posttest results were analysed using the Wilcoxon Signed Ranks Test. The findings revealed a significant improvement in students’ self-acceptance, with scores increasing from the low category to the high category (Z = -2.670, p = 0.008) and a very large effect size (r = 0.94). The study demonstrates that expressive writing therapy, when incorporated into group counselling, effectively fosters emotional regulation, psychological resilience, and self-esteem in adolescents facing family challenges. Limitations include a small sample size, absence of a control group, short intervention duration, and potential subjectivity in self-assessment. Future research is recommended to incorporate control groups, larger samples, extended interventions, longitudinal follow-ups, and qualitative approaches to deepen understanding of self-acceptance development.